2017
DOI: 10.1107/s205698901701324x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of ebastinium 3,5-dinitrobenzoate

Abstract: Ebastine, 4-(benzhydryloxy)-1-[4-(4-tert-butylphenyl)-4-oxobutyl]piperidine, reacts with 3,5-dinitrobenzoic acid in methanol solution to give the title 1:1 salt, ebastinium 3,5-dinitrobenzoate, C 32 H 40 NO 2 + ÁC 7 H 3 N 2 O 6 À . In the cation, the disubstituted aryl ring exhibits orientational disorder over two sets of atomic sites having occupancies 0.706 (4) and 0.294 (6), with a dihedral angle of 41.2 (5) between the two orientations: the bulky Ph 2 CH-O-substituent occupies an axial site on the piperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…1), which in turn forms a strong N-HÁ Á ÁO hydrogen bond to the carboxylate O4 atom of the hydrogen fumarate anion [N1Á Á ÁO4 = 2.697 (11) A ˚, Table 1]. The piperidinium ring of the cation is in the expected chair conformation, with the 4-tbutylphenyl-4-oxobutyl substituent equatorial at N1 and the diphenylmethoxy substituent axial at C4, similar to the salt described by Shaibah et al (2017), who also noted that this axial substitution is in contrast to the equatorial placement in free-base ebastine (Cheng et al, 2005;Sharma et al, 2015). The phenyl-4-oxobutyl fragment is largely planar (r.m.s.…”
Section: Structural Commentarymentioning
confidence: 96%
See 4 more Smart Citations
“…1), which in turn forms a strong N-HÁ Á ÁO hydrogen bond to the carboxylate O4 atom of the hydrogen fumarate anion [N1Á Á ÁO4 = 2.697 (11) A ˚, Table 1]. The piperidinium ring of the cation is in the expected chair conformation, with the 4-tbutylphenyl-4-oxobutyl substituent equatorial at N1 and the diphenylmethoxy substituent axial at C4, similar to the salt described by Shaibah et al (2017), who also noted that this axial substitution is in contrast to the equatorial placement in free-base ebastine (Cheng et al, 2005;Sharma et al, 2015). The phenyl-4-oxobutyl fragment is largely planar (r.m.s.…”
Section: Structural Commentarymentioning
confidence: 96%
“…Formulations of ebastine and its salts with various counter-anions have been the subject of numerous patents (see, for example, Bobee et al, 1995;Roma-Millan et al, 2011;Bilgic, 2013). In spite of this, only the crystal structures of the neutral free-base molecule (Cheng et al, 2005;Sharma et al, 2015) and the salt ebastinium 3,5-dinitrobenzoate (Shaibah et al, 2017) have been reported to date. By contrast, fumarates (di-anion fumarate and mono-anion hydrogen fumarate) are common counter-anions in compounds of pharmacological importance; examples include opipramolium fumarate (Siddegowda et al, 2011), cinnarizinium fumarate (Kavitha et al, 2013) (technically, both hydrogen fumarates), and the recently reported structure of bis(4-acetoxy-N,N-dimethyltryptammonium)fumarate, a new crystalline form of psilacetin (Chadeayne et al, 2019).…”
Section: Chemical Contextmentioning
confidence: 99%
See 3 more Smart Citations